2014
DOI: 10.5815/ijeme.2014.02.02
|View full text |Cite
|
Sign up to set email alerts
|

EFL Teachers’ Perceptions of Learner Autonomy and Their Classroom Practices: A Case Study

Abstract: It is considered that learner autonomy places a great emphasis on learners" role as independent learners who are able to take control over their learning. That is not to say, teachers become redundant in a classroom. In contrast, the key role of the teacher is to create and maintain learning community. Accordingly, this study attempted to investigate EFL teachers" perceptions of the promotion of learner autonomy and their teaching practices in a Thai context. It was quantitative-focused research, so data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 5 publications
3
27
0
Order By: Relevance
“…Thus, the majority of the teachers believe that autonomy can be developed outside the classroom through the activities undertaken by learners on their own and that these activities are effective ways of promoting learner autonomy. This finding is in line with previous studies such as Borg and Al-Busaidi(2012), Duong (2014) and Salimi and Ansari (2015).…”
Section: Table2 Technical Perspectives On Learner Autonomysupporting
confidence: 83%
See 3 more Smart Citations
“…Thus, the majority of the teachers believe that autonomy can be developed outside the classroom through the activities undertaken by learners on their own and that these activities are effective ways of promoting learner autonomy. This finding is in line with previous studies such as Borg and Al-Busaidi(2012), Duong (2014) and Salimi and Ansari (2015).…”
Section: Table2 Technical Perspectives On Learner Autonomysupporting
confidence: 83%
“…So they can manage and evaluate their own learning in the learning process. This is consistent with Duong (2014) and Najmeh et al (2015).…”
Section: Teachers' Beliefs and Feelings About Autonomous Learnerssupporting
confidence: 82%
See 2 more Smart Citations
“…Findings highlighted the strategies and skills that teachers believed to be useful in improving individual learning. Al Asmari (2013) and Duong (2014) explored EFL teachers" understanding and practices of learner autonomy. It was concluded that teachers believed that learners should have freedom to make decisions and be active in their EFL learning.…”
Section: Previous Studiesmentioning
confidence: 99%